1994
DOI: 10.1295/polymj.26.561
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modified Polymer Microspheres Obtained by the Emulsion Copolymerization of 2-Methacryloyloxyethyl Phosphorylcholine with Various Vinyl Monomers

Abstract: ABSTRACT:A series of copolymer microspheres of2-methacryloyloxyethyl phosphorylcholine (MPC) with comonomers (M) such as methyl-(MMA), ethyl-(EMA), n-butyl-(BMA), hexyl methacrylate (HMA), and styrene (St), poly(MPC-co-M), was prepared from the emulsifier-free emulsion copolymerization. From the kinetics of copolymerization of MPC and MMA, it was found that the initial rate of polymerization of MMA increased drastically in the presence of small amounts of MPC. A decrease in the yield of poly(MPC-co-MMA) micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 22 publications
0
50
0
Order By: Relevance
“…Taking into account the fact that the hydrophilic segment tends to reorganize to minimize the energy depending on the surface condition in the copolymer consists of two kinds of segments with different surface free energy, 2 • 15 a preferential existence would be expected for the PMPC segment of PMPC-b-PDMS at the water-contacting interface. 9 The silicone rubber sheds water well, while PMPC-b-PDMS shows an improved wettability due to the PMPC segment. The static contact angles (8) were measured in order to evaluate the wettability of PMPC-b-PDMS.…”
Section: Synthesis and Characterization Of Pmpc-b-pdmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the fact that the hydrophilic segment tends to reorganize to minimize the energy depending on the surface condition in the copolymer consists of two kinds of segments with different surface free energy, 2 • 15 a preferential existence would be expected for the PMPC segment of PMPC-b-PDMS at the water-contacting interface. 9 The silicone rubber sheds water well, while PMPC-b-PDMS shows an improved wettability due to the PMPC segment. The static contact angles (8) were measured in order to evaluate the wettability of PMPC-b-PDMS.…”
Section: Synthesis and Characterization Of Pmpc-b-pdmsmentioning
confidence: 99%
“…MPC was synthesized as described in a previous paper. 9 Crystallized and lypophilized bovine serum albumin (Alb, Sigma Chemicals), human serum y-globulin (Glo, Wako Pure Chemicals) and bovine serum fibrinogen (Fib, Sigma Chemicals) were used as obtained.…”
Section: Reagentsmentioning
confidence: 99%
“…Sugiyama et al reported that poly(MPC-co-MMA) microsphere could be obtained in best yield when the concentration ofMPC was 1 mo!% ofMMA in feed 23 and that many aggregation polymers can be obtained under other conditions. Thus, according to the suggestion for the MPC concentration reported by Sugiyama,23 TPM concentration was determined to be 1 mol¾ of MMA in feed. The concentration ofTPM in the solution was 1 x 10-2 moll-1 , which was over the CMC (3.6 x 10-3 mol l-1 ) ofTPM in water.…”
Section: Preparation Of Polymer Microspherementioning
confidence: 99%
“…5 -s In previous papers, the authors reported that MPC as well as 2-acryloyloxyethyl phosphorylcholine (APC) copolymerize with various vinyl monomers in soap-free emulsion polymerization to yield copolymer microspheres, on whose surfaces the phosphorylcholine moiety is concentrated. 9 • 10 The emulsion polymerization of styrene (St) initiated with an amphiphilic azo-initiator, 2-[ (2-ethylphosphatoethyl)dimeth ylammonio ]-ethyl 4,4'-azobis (4-cyanovalerate) (EAP-501), gives poly(St) microspheres whose surfaces are also modified with an analogous structure to the polar head group of phosphatidyl choline. 11 These polymer microspheres were found to reduce protein adsorption on the surface of the particles.…”
mentioning
confidence: 99%
“…12 -16 Since Kitazawa et al 17 recently synthesized the saccharide-bound monomers, for instance, 2-(glucosyloxy)ethyl methacrylate (GEMA) by a one-step process without any protective groups, the GEMA unit containing copolymers are prepared and characterized as the pharmacological and biomedical materials_ 1s, 19 In the course of our study on the functionalized polymer microspheres, 9 • 10 • 20 • 21 our interest was directed to the immobilization of both the phosphorylcholine analogous and monosaccharide moieties on the surface of polymer microspheres to produce a surface similar to a biomembrane. The present article describes on the soap-free emulsion copolymerization.…”
mentioning
confidence: 99%